Racial Equity:: reflections on afroconvenience and the brazilian quota system - Santos, Fábio Júnio Barbosa; Silva, Jaciely Soares da (Revista Labor, 2022)
The present article aims to problematize the term afroconvenience, and discuss how this, even if taken from an individual action, has directly impacted the correct implementation of affirmative policies as is the case of Law nº 12.711/2012. We propose to discuss not only how Afroconvenience has been present in contests and selection processes, but also how institutions that are victims of this type of fraud have a fundamental role in the treatment of complaints. In the end, we defend, among other aspects, the fight against the lack that we still have of a homogeneous and democratic system that allows a verification not only based on the physical aspects, but that is conducted by a bank that is specialized and knowledgeable of the different contexts and realities of Brazil, that legitimizes the legislation and that covers both its applicability and its deviations. We hope that this article can contribute with new researches and discussions on the theme, which helps to stimulate the study and dialogue on the equity of the Brazilian people's rights.